Long-term modulatory effect of Mycobacterium vaccae treatment on histopathologic changes in a murine model of asthma - (:unkn) unknown (ELSEVIER SCIENCE INC, 2007)
Background: Mycobacteria are being investigated for modulation of inflammation in asthma and atopic disorders by eliciting particularly strong protective T(H)1 immune responses. Objective: To investigate the long-term effects of intratracheally administered Mycobacterium vaccae on an experimental murine model of asthma. Methods: BALB/c mice were placed in 4 groups: long-term M vaccae, M vaccae, asthma, and control groups. All groups but controls were sensitized intraperitoneally and challenged intratracheally with ovalbumin. The long-term M vaccae and M vaccae groups were treated with M vaccae intratracheally simultaneously during challenges. Finally, mice in the long-term M vaccae group were rechallenged with ovalbumin nebulization 24 days later. Evaluations of lung histopathologic findings and serum cytokine levels were performed. Results: Comparison of the long-term M vaccae group with the asthma model group revealed that the number of hyperplasic goblet cells in small and large airways (small airway: P < .05; large airways: P < .01) and thickness of basement membrane in large airways were significantly less in the long-term M vaccae group. Furthermore, numbers of hyperplasic goblet cells in small airways (P < .05) and basement membrane in the large airway (P < .05), as well as inflammation in small airways (P < .01), were significantly less in the M vaccae group when compared with the asthma model group. Interferon-gamma secretion from splenocytes of the M vaccae group was significantly higher than the asthma model and long-term M vaccae groups. Conclusion: Intratracheal administration of M vaccae exerted a long-lasting ameliorating effect on airway histopathologic features of a murine asthma model.
Keywords: AIRWAY EOSINOPHILIA; INFLAMMATION; INFECTION; MICE